Acil Jukung: Peran Perempuan Kuin Dalam Melestarikan Jukung Sebagai Alat Transportasi Masyarakat Sungai - Istiani, Risna; Hakim, Arif Rahman; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2024)
Historically, jukung has an important role for the Kuin Kacil community, and women who are commonly called acil are more dominant in using jukung than men. This study aims to describe the activities of the Kuin Kacil community who use jukung, and analyze the role of women in the preservation of jukung. This research uses a qualitative method. The research was conducted in Kuin Kacil, Mantuil Village, Banjarmasin City, from May 2022 to November 2022. Data collection techniques used observation, in-depth interviews and documentation. Data analysis techniques through the stages of data reduction, data presentation and conclusion drawing. The results showed that women in Kuin Kacil predominantly use jukung as a means of transportation, so the role of women in preserving jukung is very important. Jukung is considered more practical and in accordance with the characteristics of women who are more feminist. In addition, other transportation is considered less feasible to use in Kuin Kacil due to narrow road access. The existence of women who use jukung as a means of transportation is one of the reciprocal relationships to the existence of the jukung itself as a means of transportation. However, the existence of jukung as a means of transportation has the potential to be abandoned as the times develop. The younger generation prefers to use land transportation, such as two-wheeled vehicles. The younger generation considers jukung as an outdated and less modern (fashionable) means of transportation to be used in the present. Jukung preservation efforts are important as a cultural heritage of river communities, and as a means of transportation that is friendly to women and nature.